2019
DOI: 10.1093/dote/doz001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of lymphovascular invasion in lymph node-negative superficial esophageal squamous cell carcinoma

Abstract: SUMMARY The relationship between lymphovascular invasion (LVI) and prognosis in patients with superficial esophageal squamous cell carcinoma (SESCC) is unclear. The aim of this study is to evaluate prognostic factors in patients with lymph node-negative SESCC. A total of 195 patients with pathologically confirmed T1a-MM, T1b, and lymph node-negative SESCC were retrospectively reviewed in this study. Overall, the disease-free survival (DFS) rate was poorer in the lymphatic invasion-positive group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The clinicopathological data revealed that patients with LVI had higher pN stage than patients without LVI, which was consistent with the cN stage results. Clinically, LVI may be an upgrade factor for all N stages (54), particularly in patients with negative lymph node metastases, for it is the only factor that affects the prognosis (55). In our study, the radiomics model achieved AUCs of 0.847 and 0.826 in the training and testing cohort, which were better than the AUCs of the clinical model (0.775 and 0.798, respectively).…”
Section: Discussionmentioning
confidence: 50%
“…The clinicopathological data revealed that patients with LVI had higher pN stage than patients without LVI, which was consistent with the cN stage results. Clinically, LVI may be an upgrade factor for all N stages (54), particularly in patients with negative lymph node metastases, for it is the only factor that affects the prognosis (55). In our study, the radiomics model achieved AUCs of 0.847 and 0.826 in the training and testing cohort, which were better than the AUCs of the clinical model (0.775 and 0.798, respectively).…”
Section: Discussionmentioning
confidence: 50%
“…Different observations have been made in the literature concerning the possible reasons. J. Oguma et al [29] hypothesized that lymphatic invasion occurs first during invasion from the muscularis mucosae to the upper layer of the submucosa, and venous invasion may occur after lymphatic invasion as the tumour invades deeper layers of the submucosa. The mechanical stress generated by proliferating tumour cells and high interstitial fluid pressure may affect intratumour vascular function [25].…”
Section: Discussionmentioning
confidence: 99%
“…In several tumor entities, LVI has been shown to correlate with LNMs and with prognoses of patients (13)(14)(15)(16)(17)(18). Similar data are available for PTC (6,(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 71%
“…Lymphatic vessel invasion (LVI) has been shown to correlate with LNM and with patients' prognoses in several tumor entities (13)(14)(15)(16). In a recent study, it was found to be the only independent prognostic factor of disease free survival (DFS) in patients with lymph node-negative superficial esophageal squamous cell carcinoma (17). Even its documented absence (L0) might play some predictive role: a multicenter retrospective analysis found that no LNMs were identified in women with low-risk cervical cancer and no LVI.…”
Section: Introductionmentioning
confidence: 99%